Oxidative Dehydrogenation of Cyclohexane by Cu vs Pd Clusters: Selectivity Control by Specific Cluster Dynamics. Issue 5 (2nd January 2020) - Halder, Avik; Ha, Mai‐Anh; Zhai, Huanchen; Yang, Bing; Pellin, Michael J.; Seifert, Sönke; Alexandrova, Anastassia N.; Vajda, Stefan
Abstract: Supported subnanometer clusters can exhibit catalytic properties not observed in their bulk analogues. Partially‐oxidized Pd and Cu clusters are reported to catalyze the oxidative dehydrogenation of cyclohexane with high activity, and with distinctly different selectivity, producing primarily benzene or cyclohexene, respectively. Under the appliedreaction conditions, the structure and oxidation state of the two catalysts evolve differently, which leads to either the desorption of the cyclohexene intermediate or to its deeper dehydrogenation. Under the applied reaction conditions, the initially oxidized Pd and Cu clusters undergo partial reduction, which we show to be required for the selectivity to emerge. Both systems also have thermal access to multiple distinct structural forms yielding statistical ensembles. The structures within these ensembles evolve with the changing nature of the bound reaction intermediates differently for the two metals; the evolution is found pronounced in the Cu clusters, but only modest in Pd. Ultimately, the different selectivity observed experimentally for the Cu versus Pd clusters is controlled by differences in the collective structural and redox dynamics of their ensembles. Abstract : Cluster dynamics : Partially‐oxidized Pd and Cu clusters are reported to catalyze the oxidative dehydrogenation of cyclohexane with high activity, and with distinctly different selectivity, producing primarily benzene or cyclohexene, respectively. The extraordinary selectivity is controlled by cluster dynamics.